Identification and Characterization of microRNAS from Entamoeba histolytica HM1-IMSS - Rameshwar, Pranela; Mar Aguilar, Fermín; Trevino, Victor; Salinas Hernández, Jannet Edith; Taméz Guerrero, Marcela M.; Barrón González, María Porfiria; Morales Rubio, María Eufemia; Treviño Neávez, Jaime Francisco; Verduzco Martínez, Jorge Armando; Morales Vallarta, Mario Rodolfo; Reséndez Pérez, Diana (2013)
Background: Entamoeba histolytica is the causative agent of amebiasis, a disease that is a major source of morbidity and mortality in the developing world. MicroRNAs (miRNAs) are a large group of non-coding RNAs that play important roles in regulating gene expression and protein translation in animals. Genome-wide identification of miRNAs is a critical step to facilitating our understanding of genome organization, genome biology, evolution, and post-transcriptional regulation. Methodology/Principal Findings: We sequenced a small RNA library prepared from a culture of trophozoites of Entamoeba histolytica Strain HM1-IMSS using a deep DNA sequencing approach. Deep sequencing yielded 16 million high-quality short sequence reads containing a total of 5 million non-redundant sequence reads. Based on a bioinformatics pipeline, we found that only 0.5% of these non-redundant small RNA reads were a perfect match with the drafted E. histolytica genome. We did not find miRNA homologs in plant or animal miRNAs. We discovered 199 new potential Entamoeba histolytica miRNAs. The expression and sequence of these Ehi-miRNAs were further validated through microarray by mParaflo Microfluidic Biochip Technology. Ten potential miRNAs were additionally confirmed by real time RT-PCR analysis. Prediction of target genes matched 32 known genes and 34 hypothetical genes. Conclusions/Significance: These results show that there is a number of regulatory miRNAs in Entamoeba histolytica. The collection of miRNAs in this parasite could be used as a new platform to study genomic structure, gene regulation and networks, development, and host-parasite interactions.